Wood adhesives / Mohd Fakrimi Mahmud - Mahmud, Mohd Fakrimi (2007)
Wood adhesives are important element in wood-based processing. Most of wood products such particle board, plywood, boat construction and more, use good wood adhesives. The adhesives like urea-formaldehyde (UF), phenol formaldehyde (PF), melamine-urea formaldehyde (MF), resorcinol formaldehyde (RF), elastomeric adhesive, thermoplastic adhesive, polyvinyl acetate and others could be used for certain wood based products. This is because the strength for each wood-based products are different. Also, the combination in adhesive contents are different.